BUSINESS PLANNING FOR FACING A RECESSION 2023 - Azza, Kirana; Oliver, Alicia (SYNTIFIC, 2023)
Background. Recessions are typically defined as significant slowdowns or contractions in a nation's economic activity. When a nation endures a prolonged decline in its economy, it is referred to as a recession. Generally, this condition is defined by declining GDP (gross domestic product) for two quarters in a row. Research Purpose. To describe business planning for facing recession 2023. Research Method. The researcher used a literature review from journals, books, and the internet to gather information on the topic of business planning for facing a recession in 2023. Findings. Many journals and books found that getting ready for the possibilities and difficulties of a possible recession in 2023 starts with money and employment issues. Establish an emergency reserve, the size of which you may not realize for some time. Because a recession in 2023 can result in the layoff of a large number of people, a corporation must also control and reduce How its firm managed to survive the shock recession. Conclusion. Spend time wisely and avoid squandering it, as doing so would be harmful to both my business and myself. If more people relax amid the prospective recessions that are anticipated to occur in 2023, it would impair his business's progress and inflict ruin in the century to come.